2021
DOI: 10.24815/eej.v12i3.19166
|View full text |Cite
|
Sign up to set email alerts
|

A study of code-switching and code-mixing used on YouTube channel: A comparison of Indonesian YouTubers

Abstract: YouTube is one of the biggest platforms where people around the world can share informative videos. In YouTube, we can find the code-switching and code-mixing phenomenon easily. There are two dominant types of code-switching and code-mixing. The first type is code-switching and code-mixing used by Group 1: Indonesian YouTubers who live abroad, while the second type is code-switching and code-mixing used by Group 2: Indonesian YouTubers who live in the country.  This study aimed to find out which group switched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
2
1
0
Order By: Relevance
“…It is followed with alternation (39, 47 %) and the least frequent code-mixing type is congruent lexicalization (3,95%). From the results of this study, they are in line with Afriyanti's (2021) andYuliana's et all (2015) which showed that intrasentential and insertion is the most frequent code-switching and mixing.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…It is followed with alternation (39, 47 %) and the least frequent code-mixing type is congruent lexicalization (3,95%). From the results of this study, they are in line with Afriyanti's (2021) andYuliana's et all (2015) which showed that intrasentential and insertion is the most frequent code-switching and mixing.…”
Section: Resultssupporting
confidence: 91%
“…This study concludes that the most dominant types of code-switching and code-mixing are intrasentential and insertion which are 124 data (76, 5 %) and 86 (56, 58%). It is in line with Afriyanti's (2021) andYuliana's et all (2015). It is found that 9 (nine) purposes or reasons of using codeswitching in this study which is to intend clarification (32,9 %).…”
Section: Discussionsupporting
confidence: 90%
“…It's a deliberate maneuver to enhance the communicative quality or align with the sociocultural context of the conversation. This is further supported by observations that code mixing, especially involving English, is increasingly accepted in casual and formal interactions alike, reflecting a shift towards a more globally interconnected language use (Afryanti et al, 2021;Mawuntu et al, 2020;Meigasuri & Soethama, 2020).…”
Section: Lifementioning
confidence: 64%
“…The phenomenon of code mixing in a podcast that incorporates both English and Indonesian languages presents an intriguing topic for discussion, particularly when the participants in the podcast demonstrate multilingual proficiency. The utilization of code mixing varies across individuals, as seen by the distinct types employed by different speakers (Afryanti, et al, 2021). There exists a variation in language dominance among individuals, with certain individuals exhibiting dominance in the Indonesian language while others demonstrate dominance in the English language.…”
Section: Introductionmentioning
confidence: 99%